PENGARUH PRICE TO BOOK VALUE RATIO(PBV), PRICE TO EARNINGS RATIO (PER), DEBT TO EQUITY RATIO(DER), DAN RETURN ON ASSET(ROA) TERHADAP RETURNOF SHARE DARI PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DI PERIODE 2012-2014 - Indri Diantari Ni Ketut (Jurnal Ilmiah Akuntansi & Bisnis, 2016)
The research discusses about The Effect of Price to Book Value (PBV), Price to Earnings Ratio (PER), Debt to Equity Ratio (DER), and Return on Asset (ROA) Toward Return of Share from Mining Companies which are listing at Indonesian Stock Exchange in the Period of 2012-2014 with source of data in the form of secondary data and type of data is quantitative data obtained from financial report of mining companies which are listing at Indonesian Stock Exchange in the period of 2012-2014. The aim of this research is to find out the effect of each independent variable toward dependent variables both partially and simultaneously by using classical assumption test (normality test, multicollinearity, heteroscedasticity, and autocorrelation). Data analysis technique is using multiple linear regression analysis with the assistance of SPSS program. The result of research shows that (1) Price to Book Value (PBV) affects positively and partially toward Return of Share, (2) Price to Earnings Ratio (PER) affects negatively and partially toward Return of Share, (3) Debt to Equity Ratio (DER) affects positively, significantly and partially toward Return of Share, (4) Return on Asset (ROA) affects negatively and partially toward Return of Share, and (5) simultaneously Price to Book Value (PBV), Price to Earnings Ratio (PER), Debt to Equity Ratio (DER), and Return on Asset (ROA) affect positively and significantly toward Return of Share.